The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12964-021-00771-6
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 signaling in the development of colitis-associated cancer and its possible interplay with microRNA-155

Abstract: Ulcerative colitis (UC) has closely been associated with an increased risk of colorectal cancer. However, the exact mechanisms underlying colitis-associated cancer (CAC) development remain unclear. As a classic pattern-recognition receptor, Toll like receptor (TLR)4 is a canonical receptor for lipopolysaccharide of Gram-negative bacteria (including two CAC-associated pathogens Fusobacterium nucleatum and Salmonella), and functions as a key bridge molecule linking oncogenic infection to colonic inflammatory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 141 publications
0
28
0
1
Order By: Relevance
“…Many of these PRRs, such as TLRs, recognize pathogens from their pathogen-associated molecular patterns (PAMPS), as well as danger-associated molecular patterns (DAMPs) that come from stressed or damaged cells [ 81 , 82 ]. Signaling from TLR4 might act as a pivotal pathogen-activated tumor signal pathway in the development of CAC [ 83 , 84 ]. TLR4 binds to lipopolysaccharide (LPS) from gram-negative bacteria, such as Fusobacterium nucleatum and Salmonella [ 85 , 86 ].…”
Section: Gut Microbiome and Colitis-associated Colon Cancermentioning
confidence: 99%
“…Many of these PRRs, such as TLRs, recognize pathogens from their pathogen-associated molecular patterns (PAMPS), as well as danger-associated molecular patterns (DAMPs) that come from stressed or damaged cells [ 81 , 82 ]. Signaling from TLR4 might act as a pivotal pathogen-activated tumor signal pathway in the development of CAC [ 83 , 84 ]. TLR4 binds to lipopolysaccharide (LPS) from gram-negative bacteria, such as Fusobacterium nucleatum and Salmonella [ 85 , 86 ].…”
Section: Gut Microbiome and Colitis-associated Colon Cancermentioning
confidence: 99%
“…Numerous studies have shown that miRNAs may significantly influence cancer tumorigenesis, proliferation, invasion, and metastasis [ 41 , 44 , 45 ]. Increased expression of TLR4 is a distinctive characteristic of CAC that co-occurs with miR-155 upregulation alongside downregulation of suppressor of cytokine signaling 1 (SOCS1) and Src homology 2 domain-containing inositol-5′-phosphatase 1 in SW480 and HCT116 cancer cells [ 42 , 46 ]. This increased activation leads to constitutive STAT3 activation.…”
Section: Mirnas In the Pathogenesis Of Complications Associated With Ibdmentioning
confidence: 99%
“…This increased activation leads to constitutive STAT3 activation. Upregulated TLR4 signaling alongside upregulated miR-9, miR-25, miR-92a, and miR-301A may ultimately induce epithelial to mesenchymal transition (EMT) by targeting E-cadherin, a cell adhesion protein, to promote tumor invasion and metastasis [ 38 , 46 , 47 ].…”
Section: Mirnas In the Pathogenesis Of Complications Associated With Ibdmentioning
confidence: 99%
“…The TLR4 signaling pathway has been shown to drive tumorigenesis and exhibit some antitumor effect on TLR4 activation [ 22 , 23 ]. TLR4 serves as a key bridge molecule linking oncogenic infection to colonic inflammatory and malignant processes by inducing miR-155 expression via transcriptional and post-transcriptional mechanisms [ 24 ]. Conversely, miR-155 can also augment TLR4 signaling by targeting negative regulators SOCS1 and SHIP1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 serves as a key bridge molecule linking oncogenic infection to colonic inflammatory and malignant processes by inducing miR-155 expression via transcriptional and post-transcriptional mechanisms [ 24 ]. Conversely, miR-155 can also augment TLR4 signaling by targeting negative regulators SOCS1 and SHIP1 [ 24 ]. Regardless of the significance of an impaired intestinal barrier indicated by elevated circulating LPS levels, the role of LPS in regulating signaling pathways involved in the development of intestinal inflammation in IBD remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%